Examination of Stress Among Recruit and Incumbent Women Firefighters - Brittany S. Hollerbach; Nattinee Jitnarin; Maria D.H. Koeppel; Michelle Valenti; Shawn Beitel; Jaclyn M. Goodrich; Jefferey L. Burgess; Sara A. Jahnke (Elsevier, 2024)
Background: Firefighting is risky and impacts the mental and physical health of personnel. While most research focuses on men firefighters, recent work has highlighted mental health concerns among women including depression, anxiety, and post-traumatic stress disorder (PTSD). Social support is a known protective factor for mental health; however, women may be excluded from the supportive peer network of the firehouse. Methods: This cross-sectional study compared the prevalence of perceived stress, peer (functional) support, anxiety, depression, PTSD, chronic work discrimination and harassment, resilience, and job satisfaction in recruit (n=184) and incumbent (n=200) career women firefighters. Results: While depression and perceived stress did not differ between recruits and incumbents, recruits were more likely to score in the range of concern for anxiety (26.1% and 15.5%, respectively). Incumbents were more likely to score at risk for PTSD (16.5% and 10.3%, respectively) and more likely to report sex discrimination, sexual harassment, and sexist behaviors in the workplace. Compared to the low stress group, those who reported moderate or high stress were more likely to score in the range of concern for anxiety (OR=3.86, CI=1.76-8.89) and PTSD (OR=1.30, CI=1.15-1.47), and report poor organizational cohesion (OR=1.13, CI=1.02-1.25). Conclusion: Addressing mental health in the context of women firefighters requires a comprehensive and multi-faceted approach including collaboration between fire departments, mental health professionals, advocacy groups, and the broader community.